2005
DOI: 10.1080/01431160512331338041
|View full text |Cite
|
Sign up to set email alerts
|

Review article: Thirty years of analysing and modelling avian habitat relationships using satellite imagery data: a review

Abstract: The application of remote sensing and Geographic Information Systems (GIS) technologies provides powerful tools when used to investigate wildlife and its habitat for an analysis or modelling approach. In this context, birds have been of great and progressive value as biological and environmental indicators. In order to learn about the common approaches used-its methods, processing steps, trends, advantages and challenges-over 120 representative publications of the last 30 years that made use of satellite image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
112
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(115 citation statements)
references
References 122 publications
0
112
0
1
Order By: Relevance
“…Earth Observation studies have often led to land cover data that is derived from satellite images (Gottschalk et al 2005). An increasingly important field of remote sensing applications is wildlife habitat assessment and modelling (Clawges et al 2008;McDermid et al 2009;Tattoni et al 2012;Melin et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Earth Observation studies have often led to land cover data that is derived from satellite images (Gottschalk et al 2005). An increasingly important field of remote sensing applications is wildlife habitat assessment and modelling (Clawges et al 2008;McDermid et al 2009;Tattoni et al 2012;Melin et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Bawa et al 2002, Luoto et al 2002, Oindo and Skidmore 2002, Willis and Whittaker 2002, Honnay et al 2003, Seto et al 2004, Nichol and Lee 2005, St-Louis et al 2006). Nevertheless, a recent literature review that included over 120 studies in which satellite images were used for avian applications (Gottschalk et al 2005) showed that few studies used satellite images when focusing on avian biodiversity in urban environments (Berry et al 1998, Alberti et al 2000, Mö rtberg and Wallentinus 2000. This may be due to the fact that high spatial resolution satellite images have become widely available only since 1999 with the launch of IKONOS, and that prior to NASA's Geocover dataset (Tucker et al 2004) there were very few, if any, freely available Landsat images globally.…”
Section: Introductionmentioning
confidence: 99%
“…A species-area relationship is given by S = cA z , where S is the number of species, A is the area, c is a species richness factor and z the species accumulation rate [107]. These relationships are not generally established and vary depending on taxonomic group, size of area and land use, among others [108,109]. In some of the proposed methods, fixed species accumulation rates are still used (e.g., [77,85]), and de Schryver et al [110] show how this might influence the final results and increase the uncertainties.…”
Section: Species Diversity As a Proxy For Biodiversitymentioning
confidence: 99%